Markers of myocardial injury and inflammation after radiofrequency ablation in children and adolescents - O. L. Peregudina; K. A. Chueva; R. B. Tatarsky; D. S. Lebedev; E. Yu. Vasilyeva; E. E. Kayumova; E. S. Vasichkina (Российский кардиологический журнал)
Aim. To assess the severity of myocardial damage and inflammation after radiofrequency ablation in children and adolescents using biochemical markers.Material and methods. The study included 58 children with tachyarrhythmias (Wolff-Parkinson-White (WPW) syndrome, WPW phenomenon, atrial tachycardia, paroxysmal atrioventricular reciprocating tachycardia, ventricular tachycardia) who underwent catheter ablation from July to October 2019. Before and after surgical treatment (after 2 hours and 5 days), the blood concentrations of myocardial damage and inflammation biomarkers (myoglobin, creatine phosphokinase-MB, interleukin-8, C-reactive protein, tumor necrosis factor alpha, metalloproteinase (MMP)-2, MMP-9, heart-type fatty acid binding protein). During the operation, catheter ablation parameters (power, temperature, application duration), the localization of arrhythmogenic focus and the type of ablation catheter were recorded. Their relationship with changes in the concentration of biochemical markers before and after intervention was studied.Results. Two hours after the operation, the concentrations of myoglobin, creatine phosphokinase-MB, MMP-9, heart-type fatty acid binding protein were increased several times (p<0,05). Changes in concentrations of interleukin-8, tumor necrosis factor alpha after the operation was not revealed. On the 5th day, elevated levels of cardiac markers returned to baseline values. MMP-9 level also decreased, but was higher than the preoperative level. Using Spearman’s correlation analysis, a direct relationship was revealed between the application duration and heart-type fatty acid binding protein level.Conclusion. Radiofrequency ablation is a safe method of treating arrhythmias in children and adolescents, since there is low volume of damaged myocardium. There was a slight increase in the level of biochemical markers after ablation (myoglobin, creatine phosphokinase-MB, fatty acid binding protein, MMP-9), incomparable with their rise in acute coronary syndrome, as well as the rapid decrease in the early postoperative period.